Uma proposta de evolução do sistema Simplified Drum-Buffer-Rope para produção e distribuição para disponibilidade - Castro, Robson Flávio (2022)
The Simplified Drum-Buffer-Rope (S-DBR) is a system that encompasses the planning, scheduling, production control, and control inventory replenishment in the supply chain. S-DBR offers distinct approaches for make-to-order and make-to-stock manufacturing environments. For this research, we focus on the method applicable to make-to-stock environments, known as Make-To-Availability (MTA) in S-DBR. MTA commits to ensuring high product availability. To adapt to merchandise distribution environments, the MTA has been expanded by incorporating new rules. While this expansion isn't considered a new method by its original authors, we refer to it as Distribution-To-Availability (DTA) to differentiate it from MTA. Our previous studies on S-DBR revealed operational challenges with both MTA and DTA. Therefore, this research aims to propose enhancements for these two methods, which are supported by four specific objectives. The first objective (i) is to conduct a systematic literature review to identify suggestions and proposed improvements for S-DBR and its predecessor, DBR. The review uncovered that the previously identified problems have yet to be addressed, and studies are scarce on S-DBR compared to DBR. One of the difficulties encountered by MTA is effectively managing manufacturing environments with sequence-dependent setup time. The second (ii) and third (iii) objectives are dedicated to tackling this challenge. Objective (ii) involves identifying dispatch rules suitable for MTA, while objective (iii) focuses on proposing a solution for MTA in sequence-dependent setup time environments. In the case of DTA, the challenge lies in planning the replenishment of stock buffers within the supply chain, particularly in the distribution network. S-DBR emphasizes the need for frequent inventory allocation but does not offer a solution that effectively balances transport costs and inventory maintenance costs. Consequently, the specific objective (iv) aims to propose a solution that enables DTA to address the trade-off between transportation costs and inventory maintenance costs, ensuring both product availability and profitability. The research results demonstrate that utilizing different dispatch rules can enhance the performance of MTA. Furthermore, our proposed solution for sequence-dependent setup time environments has improved the performance of MTA. Regarding DTA, the proposed solutions effectively ensure inventory supply in the distribution network by striking a balance between transport and inventory maintenance costs, thereby maintaining product availability and profitability.